Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Manufaktur: Studi Kasus Pada Perusahaan Subsektor Makanan dan Minuman di BEI Periode 2018-2021 - Ayuningsih, Ninda; Goenawan, Yohanes August (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To determine the effect of Capital Structure (DER) and Profitability (ROE) on Company Value (PBV) in Food and Beverage Sub-Sector Manufacturing Companies on the Indonesia Stock Exchange for the 2018-2021 Period. Background Problems: Because there are still differences in research between one study and another. Novelty: Retesting the same variables by previous researchers, because there are still research differences between one study and another. Research Methods: This study uses a descriptive quantitative approach research type using secondary data on 14 companies out of 30 companies and the data analysis technique used is multiple linear regression with the help of the SPSS 25 program. Findings/Results: Based on the test results, partially Capital Structure (DER) does not have a significant effect on Company Value (PBV), partially Profitability (ROE) has a significant effect on Company Value (PBV) and together Capital Structure (DER) and Profitability (ROE) have a significant effect on Company Value (PBV). Conclusion: The company must maintain the DER ratio or increase the DER ratio, and the company's existing capital must be used optimally. The company should take a policy to increase net profit income so as not to continue to empower capital.